Penilaian Fasilitas Pejalan Kaki Berdasarkan Persepsi Pengguna dan Pedestrian Level of Service (PLOS) - Hariani, Mira Lestira; Mahardiani, Gita (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2024)
Pedestrian facilities are a crucial element in sustainable urban planning to enhance safety, comfort, and accessibility for road users. This study aims to evaluate the quality of pedestrian facilities in the Perjuangan Street corridor, Cirebon City, which is designated as an educational area, using the Customer Satisfaction Index (CSI) and Pedestrian Level of Service (PLOS) approaches. The methods employed include pedestrian surveys, user satisfaction questionnaires, and an analysis of sidewalk geometric conditions based on the 2017 technical planning guidelines. The results indicate that pedestrian satisfaction with the available facilities falls within the "very satisfied" category, with a CSI score of 90.83. Based on the PLOS analysis, the Perjuangan Street corridor is classified as grade A, meaning pedestrians can move freely without significant obstacles. However, the geometric analysis reveals that although the sidewalk width meets the standards, the surface condition is deteriorating, and there is a lack of facilities for persons with disabilities. Therefore, this study recommends improvements such as enhancing the quality of sidewalk surfaces, providing dedicated lanes for people with disabilities, adding green spaces and drainage systems, and upgrading supporting facilities such as seating, lighting, and pedestrian signs to improve user safety and comfort. Keyword: pedestrian facilities, satisfaction level, Pedestrian Level of Service, Customer Satisfaction Index, infrastructure evaluation.